2019
DOI: 10.1101/19012393
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transdiagnostic expression of interoceptive abnormalities in psychiatric conditions

Abstract: Background: Interoception, the sensing of information about the internal physiological state of the body, is proposed to be fundamental to normal and abnormal affective feelings. We undertook a cross-sectional characterisation of cardiac interoception in patients accessing secondary mental health services to understand how interoceptive abnormalities relate to psychiatric symptoms and diagnoses. Methods: Patients attending adult mental health services (205 female, 101 male) and controls (42 female, 21 male)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 56 publications
(101 reference statements)
2
14
1
Order By: Relevance
“…Across participants, cardioceptive performance in the heartbeat tracking (M = .600, SEM = .035) and the heartbeat discriminating (M = .576, SEM = .017) tasks were comparable to recent work in non-clinical subgroups (Critchley et al, 2019). For the water load test, mean gastric interoceptive performance was .588 (SEM = .018), similar to values from van Dyck et al (2016).…”
Section: Resultssupporting
confidence: 64%
“…Across participants, cardioceptive performance in the heartbeat tracking (M = .600, SEM = .035) and the heartbeat discriminating (M = .576, SEM = .017) tasks were comparable to recent work in non-clinical subgroups (Critchley et al, 2019). For the water load test, mean gastric interoceptive performance was .588 (SEM = .018), similar to values from van Dyck et al (2016).…”
Section: Resultssupporting
confidence: 64%
“…For example, one study found that a serotonergic receptor antagonist reduced activation in regions of the insula associated with interoception 85 , which could pertain to reduced perceptual accuracy. Another study found higher heart rate and lower heart rate variability in individuals on antipsychotic medications, and higher self-reported bodily awareness in individuals on antidepressant medications 74 . Yet another study showed that acute administration of a serotonin reuptake inhibitor increased metacognitive awareness of performance accuracy on a cardiac interoception task 86 .…”
Section: Discussionmentioning
confidence: 93%
“…47,[70][71][72][73] ). For example, one recent study found that a transdiagnostic patient sample (including affective disorders, schizophrenia, and personality disorders) showed lower subjective interoceptive confidence on both a heartbeat tracking task and a heartbeat discrimination task, as well as lower objective performance on the latter 74 . Other previous cardiac perception studies have reported that depressed individuals exhibit reduced accuracy on a heartbeat counting task [75][76][77] , and that performance is negatively correlated with depressive symptoms 78 as well as associated with both lower positivity and poorer decision-making 75 .…”
Section: Discussionmentioning
confidence: 99%
“…Haggard, et al explained excessive sense of agency from the standpoint of retrospective inference 2 . In addition, it was demonstrated that the relationship between interocepton and emotional face recognition in schizophrenia was opposite to any other conditions including in healthy people 35 . Further study is required to understand this complex relationship in schizophrenia.…”
Section: Discussionmentioning
confidence: 94%